Postoperative malrotation of humerus shaft fracture causes degeneration of rotator cuff and cartilage - Cheng Wang (Nature Portfolio, 2021)
Abstract We hypothesized that postoperative malrotation of humeral shaft fractures can alter the bio-mechanical environment of the shoulder; thus, rotator cuff and cartilage degeneration could be induced. Therefore, we designed an animal experiment to evaluate the impact of malrotation deformities after minimally invasive surgery for humeral fractures on the rotator cuff and cartilage, which has rarely been described in previous studies. Twenty-four New Zealand white rabbits were randomly divided into the sham control group (A), negative control group (B) and malrotated group (C). A sham operation with surgical exposure alone was performed in group A. Humeral shaft osteotomy was performed in Group B and C. In Group B, the fractures were fixed in situ with plate -screw system. While in Group C, iatrogenic rotational deformity was created after the proximal end of the fracture being internally rotated by 20 degrees and then subsequently fixed. The animals with bone healing were sacrificed for pathological and biochemical examination. In group C, the modified Mankin scale for cartilage pathology evaluation and the modified Movin scale for tendon both showed highest score among groups with statistical significance (P < 0.05); Disordered alignment and proportion of collagen I/III of rotator cuff were confirmed with picrosirius red staining; Transmission electron microscopy also showed ultrastructural tendon damage. Immunohistochemistry showed that both MMP-1 and MMP-13 expression were significantly higher in group C than groups A and B(P < 0.05). Minimally invasive techniques for humerus shaft fracture might be cosmetically advantageous, but the consequent postoperative malrotation could increase the risk of rotator cuff and cartilage degeneration. This conclusion is supported here by primary evidence from animal experiments.